O pensamento escatológico de Pierre Teilhard de Chardin - Fasano, Anderson (2009)
Objectively describe, after analysing subjectively, the Matter circunvolutions in its space-time evolution from Man, who marches to the building of his definite I was the huge challenge to Father Teilhard; and that in the present dissertation was studied along three chapters. The first chapter delineates, thus, historic contextualization of Teilhard de Chardin s work and the fundamental aspects of his Cosmovision in order to enhance through the text, the escathological mark of his thought: his methodology and epistemology, and the traces of cognitive fundamentation of his theology from theological place privileged by him in insights of this nature: the Cosmos. Besides, he had thought of the Mistery of Salvation in a christocentric perspective. His preoccupation in this specific field had its main finality to attempt to connect the Christ announced by the Church as The Savior of the World with the Universe in evolution that aims the Escathological Plenitude in the Omega, Meta-Consummatory in the sótero-cosmic-evolutive process: that was the theme that constituted the third chapter. At last, his actual and relevant systematic view of the All is also a kind of mystical contemplation of a christified Cosmos; in a transfigured Universe in the Love of God that makes His Creation always New.